2010
DOI: 10.1097/aco.0b013e32833c33ed
|View full text |Cite
|
Sign up to set email alerts
|

The scientific evidence for acute pain treatment

Abstract: It is difficult for clinicians to remain updated and synthesize all the evidence available relating to the treatment of acute pain. Assistance is available, but there may be limitations to some of the evidence presented and its application to different aspects of clinical practice and different patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…There appears to be a trend toward more use of opioid due to increased attention paid to the treatment of acute, chronic, and cancer-related pain 17 18 . Pethidine, an opioid with predominantly κ-receptor agonist properties, is a phenylpiperidine derivative with a chemical structure similar to local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a trend toward more use of opioid due to increased attention paid to the treatment of acute, chronic, and cancer-related pain 17 18 . Pethidine, an opioid with predominantly κ-receptor agonist properties, is a phenylpiperidine derivative with a chemical structure similar to local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is used as a quality indicator [ 3 5 ], and there are multiple guidelines for pain management [ 6 , 7 ]. Acute pain may have adverse physiological and psychological effects [ 8 , 9 ], but there is still inadequate treatment of pain in EDs [ 10 , 11 ]. Of the patients who arrive at the ED with a painful condition, more than 50 % indicate that the pain is moderate to severe [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians usually coping with pain, therefore, face an almost impossible task in keeping up to date with integrating all of the current evidence applicable to their personal practice. Fortunately, assistance in recording and organizing knowledge is also increasingly available and comes in a number of different forms, including systematic reviews, clinical guidelines, evidence summaries, expert reviews and analgesic "league" tables [1]. While a large amount of evidence related to acute pain treatment is available, limitations may exist in terms of its quality as well as clinical significance, especially in the areas of neuraxial anesthesia and spinal opioid selection for postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…While a large amount of evidence related to acute pain treatment is available, limitations may exist in terms of its quality as well as clinical significance, especially in the areas of neuraxial anesthesia and spinal opioid selection for postoperative pain. The quality of evidence used in evidence summaries or guidelines is often graded, and in all cases evidence obtained from meta-analyses of randomized controlled trials (RCTs) is considered to be the 'highest' level [1]. However, it has been recently suggested that meta-analyses that evaluate studies about the treatment of postoperative pain can explore clinical heterogeneity associated with variable types of surgery to arrive at better implications for clinical practice [2].…”
Section: Introductionmentioning
confidence: 99%